Lemongrass and citral effect on cytokines production by murine macrophages - Bachiega, Tatiana Fernanda [UNESP]; Sforcin, Jose Mauricio [UNESP] (Elsevier B.V., 2011)
Ethnopharmacological relevance: Cymbopogon citratus (DC) Stapf (Poaceae-Gramineae), an herb commonly known as lemongrass (LG), is an important source of ethnomedicines as well as citral, the major constituent of Cymbopogon citratus, used in perfumery, cosmetic and pharmaceutical industries for controlling pathogens. Thus, the goal of this work was to analyze the effect of LG and citral on cytokines production (IL-1 beta, IL-6 and IL-10) in vitro, as well as before or after LPS incubation.Materials and methods: Peritoneal macrophages from BALB/c mice were treated with LG or citral in different concentrations for 24 h. The concentrations that inhibited cytokines production were tested before or after macrophages challenge with LPS, in order to evaluate a possible anti-inflammatory action. Supernatants of cell cultures were used for cytokines determination by ELISA.Results: As to IL-1 beta. only citral inhibited its release, exerting an efficient action before LPS challenge. LG and citral inhibited IL-6 release. Cymbopogon citratus showed inhibitory effects only after LPS challenge, whereas citral prevented efficiently LPS effects before and after LPS addition. Citral inhibited IL-10 production and although LG did not inhibit its production, the concentration of 100 mu g/well was tested in the LPS-challenge protocol, because it inhibited IL-6 production. LG inhibited LPS action after macrophages incubation with LPS, while citral counteracted LPS action when added before or after LPS incubation.Conclusion: LG exerted an anti-inflammatory action and citral may be involved in its inhibitory effects on cytokines production. We suggest that a possible mechanism involved in such results could be the inhibition of the transcription factor NF-kappa B. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cymbopogon citratus; Lemongrass; Citral; Immunomodulation; Cytokines